Evaluating Bank DJX's Cybersecurity Maturity Level from Indonesia's Regulatory Perspective - Hidayat, Rahmat Rian; Husna, Juniana; Akbar, Son Ali (Journal of Information Technology and Its Utilization, 2025)
In the digitalization era of banking, cybersecurity has become a critical priority as the frequency and sophistication of cyber-attacks rise. This study evaluates Bank DJX's cybersecurity maturity (a pseudonym), focusing on compliance with POJK PTI and SEOJK regulations on cyber resilience in commercial banks. Using a qualitative approach, it assesses inherent cybersecurity risks and the effectiveness of risk management. Findings show a maturity score of 2.1, indicating effective and satisfactory practices, alongside an inherent risk score of 1.9 with a narrow gap (+0.20), suggesting that while current controls address existing threats, the capacity to manage emerging risks remains limited without further enhancements. Given the rapidly evolving threat landscape, continuous improvement is essential. Aligned with recommendations, Bank DJX is well-positioned to strengthen its cybersecurity resilience to meet regulatory demands and proactively address future threats. This study offers empirical insights into cybersecurity practices in Indonesia's digital banking sector, underscoring the importance of regulatory compliance and proactive risk management.